Selective enrichment of active bacterial taxa in the Microcystis associated microbiome during colony growth - Carolina Croci; Gabriela Martínez de la Escalera; Carla Kruk; Angel Segura; Susana Deus Alvarez; Claudia Piccini (PeerJ)
The toxic cyanobacterium Microcystis causes worldwide health concerns, being frequently found in freshwater and estuarine ecosystems. Under natural conditions, Microcystis spp. show a colonial lifestyle involving a phycosphere populated by a highly diverse associated microbiome. In a previous study, we have proposed that colony formation and growth may be achieved through mechanisms of multispecies bacterial biofilm formation. Starting with single-cells, specific bacteria would be recruited from the environment to attach and create a buoyant biofilm or colony. This progression from a few single cells to large colonies would encompass the growth of the Microcystis community and bloom formation. In order to test this, we applied 16S rDNA metabarcoding to evaluate the changes in bacterial community structure (gDNA) and its active portion (cDNA) between different sample sizes obtained from a Microcystis bloom. Bloom sample was sieved by size, from one or a few cells (U fraction) to large colonies (maximum linear dimension ≥ 150 µm; L fraction), including small (20–60 µm, S fraction) and medium size (60–150 µm, M fraction) colonies. We found that gDNA- and cDNA-based bacterial assemblages significantly differed mostly due to the presence of different taxa that became active among the different sizes. The compositional variations in the communities between the assessed sample sizes were mainly attributed to turnover. From U to M fractions the turnover was a result of selection processes, while between M and L fractions stochastic processes were likely responsible for the changes. The results suggest that colony formation and growth are a consequence of mechanisms accounting for recruitment and selection of specific bacterial groups, which activate or stop growing through the different phases of the biofilm formation. When the final phase (L fraction colonies) is reached the colonies start to disaggregate (bloom decay), few cells or single cells are released and they can start new biofilms when conditions are suitable (bloom development).